2019
DOI: 10.2305/iucn.ch.2019.parks-25-1tda.en
|View full text |Cite
|
Sign up to set email alerts
|

People’s perceptions of protected areas across spatial scales

Abstract: The relationships that local communities have with protected areas are important for the success of these areas. However, it is difficult to capture park-people relationships at spatial scales that make them useful for conservation management and planning. To explore the role of scale in people's perceptions of protected areas, we examined the relative contribution of factors at different levels (i.e. village, protected area, country) to people's attitudes and perceptions of protected areas. Based on 3,573 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
3
1
0
Order By: Relevance
“…This finding was in line with previous research that demonstrated a direct effect between young people's attitudes and intentions to adopt specific pro-environmental behaviours, such as green consumption [105], purchasing of pro-environmental products [13], pollution emissions reduction [39], the choice of transport mode [106], as well as conservation and recycling behaviours [88,107]. Regarding nature parks, our findings were consistent with recent studies [108,109] that highlighted the prevalence of positive attitudes. This can be explained by the fact that while protected areas may entail costs for young people, the numerous benefits they provide are often more widely perceived than the costs incurred.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was in line with previous research that demonstrated a direct effect between young people's attitudes and intentions to adopt specific pro-environmental behaviours, such as green consumption [105], purchasing of pro-environmental products [13], pollution emissions reduction [39], the choice of transport mode [106], as well as conservation and recycling behaviours [88,107]. Regarding nature parks, our findings were consistent with recent studies [108,109] that highlighted the prevalence of positive attitudes. This can be explained by the fact that while protected areas may entail costs for young people, the numerous benefits they provide are often more widely perceived than the costs incurred.…”
Section: Discussionsupporting
confidence: 93%
“…From the perspective of total effects, conservation costs had a significant negative impact on conservation willingness and behaviors. This conclusion is consistent with the findings of other scholars [46,59,60]. Most residents believed that conservation behaviors increased the economic cost of living without increasing economic benefits.…”
Section: Analysis Of Factors Influencing Community Residents' Conserv...supporting
confidence: 92%
“…Wang's [50] survey of communities around the Qinling Nature Reserve in China found that crops in the community were often damaged by wild boars, hares and black bears, causing serious economic losses to farmers; By studying farmers' perceptions of cost-benefit in the neighborhood of seven national parks in the Indian and Nepalese regions, Karanth and Nepal [37] found that farmers' perceptions of benefits were insensitive, while perceptions of costs were very sensitive. Other scholars have shown that people who are victims of wildlife depredation or have limited access to forest resources may exhibit negative perceptions and attitudes towards nearby protected areas [51]. This is consistent with the findings of this study.…”
Section: Factors Affecting Community Participation In Protection Actionsupporting
confidence: 92%